Criticism of Islamic philosophy at the thinkers of Islam - رمضان شمة افراح (Al-Adab Journal, 2018)
The question of the existence of God the key issue that had occupied human thought of the foot, and the philosophy since its inception to focus on proving the existence of the Creator of the universe and the many philosophers leg evidence for it. But this evidence was severely criticized. Thus weakening the power of inference philosophers by .oaldrash at hand may have a width not strong evidence adopted by the philosophers to prove the existence of the Creator of the universe with criticism directed it. The conclusions of the study that the evidence presented by the philosophers of the existence of God does not live up to be damning evidence of doubts the driving force for suspicion, and it does not have the introductions of Nha non-Muslim in the right minds and contradictory and discomfiture, and this enabled the scientists face a lot criticism has argued the invalidity of the inference. Hence, the urgent call to all those in charge of formulating doctrine curricula in the Muslim world now that behave approach to the Quran in the inferred matters Islamic faith., Not of Nha evidence uncertain conclusive doubts ¸baida for contradiction, suitable for the minds of different levels, to other characteristics that are unique evidence of the Koran.